Database Management Challenges and Solutions in IoT Environments: A Systematic Literature Review - Ahmad Ferdaws Ahmadi; Esmatullah Hadi; Shahvali Karimi; Reshad Ahmadi; Farid Hassani (Tinta Emas Publisher, 2024)
The rapid proliferation of Internet of Things (IoT) devices has led to an unprecedented volume and velocity of data generation, posing significant challenges for database management. This study investigates the complexities of database management within IoT environments and explores effective methods for addressing key obstacles. Through a comprehensive literature review and analysis of existing research, the study examines how database management systems handle the immense volume and speed of data from IoT devices. It also explores methods for ensuring data security and privacy amidst the diverse data types and dynamic nature of IoT systems. Furthermore, the study assesses the potential of emerging technologies like blockchain and edge computing in addressing scalability challenges in IoT database management. The findings underscore the critical importance of scalable infrastructure, distributed computing, and optimized processing techniques in effectively managing IoT-generated data. Recommendations are provided for organizations to leverage innovative approaches and technologies to overcome the challenges posed by the IoT data landscape. Ultimately, this study contributes to advancing understanding in the field of IoT database management and provides insights for future research and development efforts.